ILLOCUTIONARY ACTS IN “THE FAULT IN OUR STARS” MOVIE - Syahrul Efendi Lubis (Rahis Cendekia Indonesia, 2024)
This research entitled “An Analysis of Illocutionary Acts in The Fault in Our Stars” proposed by John R. Searle. However, this thesis limits the study of illocutionary acts only to directive and commissive type. Directive is illocutionary act which by uttering this type, a speaker gets the hearer to do certain action, for example ordering, asking, requesting, etc. While commissive is illocutionary act which by uttering this type, a speaker commits himself to do certain action, for example promising, threatening, guaranteeing, etc. This research used quotations of The Fault in Our Stars movie taken from a website as data to be analyzed. The research used descriptive qualitative research as method to do the research. The Fault in Our Stars movie character uses directive type to request, to implore, to advise, to order, to demand, to command, or to challenge the hearers to do certain actions, to forbid the hearers of doing something, and to ask questions so that the other characters of the movie provide information, give confirmation, give opinion, further explanation, etc. While by uttering commissive type, they promise the hearers that they as speakers will do certain future action, for example promising to do something.